Justice Development and Peace Commission (JDPC) on women empowerment - Ogunyemi, Segilola Yewande; Adisa, Ademola Lateef; Adenuga, Ademolu Oluwaseun (Journal of Gender and Power, 2020)
The need to empower women seems to center on the fact that women have potentials to contribute to the development process but are constrained by some factors that render them powerless. For this reason, this study examined the impact of justice development and peace commission on women empowerment by assessing the empowerment initiatives, women participation and identifying factors that militate against full empowerment and participation of women. The theoretical background for this study is structural functionalism and the study is descriptive in nature. The study was conducted in JDPC, Ijebu-Ode and data was collected from primary and secondary sources. For primary data, IDI was conducted for 12 beneficiaries of the empowerment programmes and 6 employees of JDPC while secondary data were collected through extensive review of literature. The data collected were content analyzed. The findings revealed that not until recent empowerment programmes organized for women, women do not have the zeal for the programmes which has limited their consciousness and strength in the society. Also, awkward spending of women contributed to their failure from receiving further loans from JDPC. Equally, low level of education, tradition and belief that men are better than women affected the slow rate of empowerment of women.